PENGARUH TATA LETAK BANGUNAN TERHADAP GAYA GELOMBANG TSUNAMI - , Benazir, Prof. Ir. Radianta Triatmadja, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Today tsunami hazard has become an important aspect in national security of coastal area of Indonesia. Tsunami disaster in the Indian Ocean 2004 has caused a lot of buildings damaged and probably the greatest loss of lives ever due to tsunami. Aceh district suffered the greatest losses in terms of damage to infrastructures and loss of lives. The incident has made Aceh realized that they too are vulnerable to tsunami. After the tsunami of 26 December 2004, Aceh once again struck by a tsunami in the area of Simeulue and Nias Islands on 26 March 2005. Yet another potential earthquake generated tsunami measuring over 8 on the Richter Scale occurred in Aceh on 11 April 2012 which resulted in a low tide in Ulee Lheue Beach Banda Aceh. Although the earthquake did not generate tsunami, it has made Acehnese more alert and learned how to prepare against such horrible hazard. After The Indian Ocean Tsunami 2004 in Aceh, houses and other buildings were reconstructed by government, LSM, and Non-Governmental Organization (NGO). The new buildings near the coast line are open directly to tsunami attack. This research aims to analyze the tsunami force on buildings of different types, and the effect of other buildings nearby. The research was conducted using physical model at the Hydraulic and Hydrology Laboratory, Research Centre for Engineering Science, Gadjah Mada University Indonesia. The physical model simulations were carried out in a wave flume of 24 m long, 1.45 m wide, and 1.5 m high, that was facilitated with tsunami generator based on dam break system. The building models were made of plywood and were placed in a row perpendicular to the flume. The distance between the buildings was varied to observe the effect of the gaps. The result shows that tsunami force is greater on high building due to larger projected area exposed to tsunami. Based on the application of a new formula obtained from the research ð¹ = 1 2 ðð ( (ð¹ð1+22)2ð»1)2, the force on high building is 69% greater than on the low building. Tsunami force also depends on the gap between buildings. The narrower is gap the greater is the force. A new formula is proposed to predict tsunami force on row of group buildings separated by gaps, that is ð¹ =ð¶ðððð2(ð´ð´â²)0.534ðºâ0.136 (the value of Cfg is 1.05 for overtopping building and 1.59 for non-overtopping building).